A comunicação popular, o debate e o processo constituinte no Brasil (1977 - 1988) - BARBOSA, Mariana de Oliveira Lopes (2012)
The period and theme that will be addressed in this dissertations concerns the debate and the constitutional process of formulation of the 1988 Constitution in Brazil, which began in 1977 on the occasion of the beginning of the distension and slow and gradual political opening of the New Republic Military Dictatorship, therefore, defined as the time frame between 1977 and 1988, in other words, the release of the package in April and early discussions on the Constituent Assembly the enactment of the Constitution in October 1988. All these process will be seen through the historical social movements and their role in Popular Communication, which, in contrast to mass media promoted a Constituent politicizing the process.